Penegakan Hukum Terhadap Tindak Pidana Penyelundupan Pakaian Bekas Dihubungkan Dengan Undang-Undang Nomor 10 Tahun 1995 Tentang Kepabeanan - Yoga Gintara; Chepi Ali Firman Zakaria (UNISBA Press, 2022)
Abstract. Law enforcement is believed to guarantee and protect the interests of the community. Prohibition of importing used clothes Minister of Industry and Trade Decree Number: 229/MPP/Kep/7/1997, Article 3 for health reasons, furthermore, smuggling of used clothes violates Article 102 letter (a) of Law Number: 17 of 2006 concerning Amendments to Law Law Number: 10 of 1995 concerning Customs. Then in the context of the Tanjung Balai Karimun District Court Number 23/pidsus/2020/Pn Tbk there is a disparity in decisions when compared to the Tanjung Balai Asahan District Court Number 243/Pid.B/2017/PN Tjb. The lack of investigations considered by the council has made the act of smuggling used clothes not yet providing a deterrent effect in suppressing the progress of the case. The author's assessment in making the decision on Decision Number: Balai Karimun Number: 23/Pid.Sus/2020/Pn Tbk is still not optimal if it is related to the purpose of punishment as an effort to retaliate and prevent the recurrence of the crime of smuggling. Abstrak. Penegakan hukum diyakini untuk menjamin dan melindungi kepentingan masyarakat. Laranagn mengimpor pakain bekas KepMen Perindustrian dan Perdagangan Nomor : 229/MPP/Kep/7/1997, Pasal 3 dengan alasan keshatan, selanjutnya penyelundupan pakaina bekas melanggar Pasal 102 huruf (a) Undang-undang Nomor : 17 Tahun 2006 Tentang Perubahan Atas Undang-undang Nomor : 10 Tahun 1995 Tentang Kepabeanan. Kemudian pada konteks PN Tanjung Balai Karimun Nomor 23/pidsus/2020/Pn Tbk terjadinya disparitas putusan jika dibandingkan dengan PN Tanjung Balai Asahan Nomor 243/Pid.B/2017/PN Tjb. Masih kurangnya penelusuran yang dipertimbangankan oleh majlis menjadikan tindak penyelundapan pakain bekas belum memebrikan efekjera dalam menekan lajunya kasus tersebut. Penilain penulis daalam membrikan putusan pada Putusan Nomor: Balai Karimun Nomor: 23/Pid.Sus/2020/Pn Tbk masih belum maksimal jika dikaitakan dengan tujuan pemidaan sebagai upya pembalasan dan pencegahan agar tidak terulang laginya tindak pidana penyelundupan.